Ethnic Musical Culture of Moscow Mari (II) - Marina V. Kutsaeva (Publishing house "Sreda", 2020)
The article deals with the problem of maintaining and preserving the ethnic musical culture of the Mari people in the conditions of the diaspora. The purpose of the article is to determine the prospects for preserving the ethnic musical culture of members of the Mari diaspora in the framework of integration processes in the multicultural Moscow region. Methods. The article is based on the data obtained when conducting a sociolinguistic survey in the Mari diaspora of the Moscow region; the selective sampling include 100 respondents, all of them are natives of the Republic of Mari El or places of traditional compact settlement of the Mari ethnic group, currently living in Moscow or in the Moscow region. One of the aspects of the survey was to study the respondents' language loyalty, which indirectly manifests itself in in the knowledge and observance of ethnic musical culture. In particular, the respondents were asked questions about the language or languages in which they are likely to sing or listen to songs, about the value and significance of Mari songs in their lives. Based on their answers, tables, reflecting the results, were drawn. Results. According to the results of the sociolinguistic survey in the Mari diaspora, a vast majority of the respondents (96%) listen to (and/or sing) songs in their ethnic language one way or another, under completely different circumstances and using a wide range of modern technologies and telecommunications. The representatives of the Mari Diaspora take an active part in various cultural and musical events, which are held not only within the framework of the ethnic Mari community in Moscow, but also on the private initiative of young Mari activists. The author concludes that the ethnic musical culture, which the members of the Diaspora maintain both independently and in groups, undoubtedly plays an important role in uniting the Moscow Mari people and attracting new members of the Mari Diaspora, it slows down assimilation processes and contributes to the preservation of their ethnic and cultural identity.